2001
DOI: 10.1097/00006534-200106000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Long Head of the Triceps Brachii as a Free Functioning Muscle Transfer

Abstract: This anatomic study investigates the possibility of using the long head of the triceps brachii muscle as a free functioning muscle transfer for the upper limb. It has been reported that the long head is not difficult to harvest and that its loss does not create significant donor-site morbidity. The muscle was studied in 23 fresh frozen upper limbs. The long head in all 23 specimens had a constant and proximal vascular pedicle from the profunda brachii artery and vein. The mean pedicle was long (4 cm) and had l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Travill showed that among the three heads of the triceps the long head played the least important role whereas the medial and the lateral heads showed a considerable amount of activity during elbow extension. The long head of the triceps has been transferred as a pedicled musculo‐cutaneous flap and can also be used for a free functioning muscle transfer (Travill,1962; Hartrampf et al,1990; Hallock,1993; Lim et al,2001; Sundine and Malkani,2002). We selected the nerve to the long head of the triceps because it could directly reach the level of the anterior branch of the axillary nerve without nerve grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Travill showed that among the three heads of the triceps the long head played the least important role whereas the medial and the lateral heads showed a considerable amount of activity during elbow extension. The long head of the triceps has been transferred as a pedicled musculo‐cutaneous flap and can also be used for a free functioning muscle transfer (Travill,1962; Hartrampf et al,1990; Hallock,1993; Lim et al,2001; Sundine and Malkani,2002). We selected the nerve to the long head of the triceps because it could directly reach the level of the anterior branch of the axillary nerve without nerve grafting.…”
Section: Discussionmentioning
confidence: 99%
“…[38] The long head of triceps has been transferred for axillary contracture[39] and as a free functioning muscle transfer. [40] Leechavengvong et al . [41] reported seven patients with C5 and C6 avulsion injuries who underwent double nerve transfers (distal spinal accessory nerve to suprascapular nerve and long head triceps branch to anterior branch of axillary nerve).…”
Section: Discussionmentioning
confidence: 99%
“…Use of a single branch does not sacrifice elbow extension as evidenced by its recognized use in muscle flaps [15,16].…”
Section: Triceps Nerve Branch To Axillary Nervementioning
confidence: 99%